In vivo metabolism of 2-[1 '-phenyl-3 '-(3chlorophenyl)-2 '-propenylyden]hydrazino-3-methyl-4(3H)-quinazolinone in rats - (:unkn) unknown (SPRINGER FRANCE, 2005)
The aim of this study was to investigate by HPLC the in vivo metabolism of 2-[1'-phenyl-3'-(3-chlorophenyl)-2'propenylyden]hydrazino-3-methyl-4(3H)-quinazolinone as a substrate, and as a model compound in rats. The substrate was dissolved in DMSO/water (1:4) and administered intraperitoneally at a dose of 100 mg/kg in a volume of approximately 0.1 mL. Blood samples were taken before and 30 min, 1.5, 3, 6, 9, 11, 30 and 48 h after i.p. drug administration. The chromatographic separation of the substrate and its metabolites was performed using a stainless steel Novopak C18 column (150 x 4.6 mm i.d., 5-mu m particle size). The optimal composition of the mobile phase was reached by introducing different mixtures of pure acetonitrile and water in a linear gradient system. Following the biotransformation of this compound, 2-hydrazino-3-methyl-4(3H)-quinazolinone (M1) and 3-(3-chlorophenyl)-1-phenylprop-2-en-1-one (M2) derivatives were identified together with substrate by comparing them to reference standards using HPLC-UV/DAD. In addition, the composition of these metabolites and substrate was confirmed by LC-MS in plasma.
Keywords: 2-[1-phenyl-3-(chlorophenyl)-2-propenylyden]hydrazino-3-methyl4(3H)-quinazolinone; HPLC; in vivo metabolism; ANTIMYCOBACTERIAL ACTIVITY; ANTICONVULSANT ACTIVITY; ANTITUBERCULAR ACTIVITY; ANTIMICROBIAL ACTIVITY; HYDRAZONE DERIVATIVES; ANTIFUNGAL ACTIVITY; HYDRAZIDES; SCHIFF; BASES